Music Assessment Techniques for Evaluating the Students’ Musical Learning and Performance in the Philippine K-12 Basic Education Curriculum - Tabuena, Almighty Cortezo; Morales, Glinore Santiago; Perez, Mary Leigh Ann Corpuz (Harmonia: Journal of Arts Research and Education, 2021)
The primary objective of this study is to review and characterize research-based music assessments that might be used to guide and assist teachers and students in transforming their attitudes and perceptions, ability to express their ideas and concepts during the assessment process openly. This study employed descriptive and autoethnographic methods to elicit information about current conditions and practices through the library approach and literature review. The identified music assessment techniques were used to determine how well students comprehend important points in a session. It includes the Music Concept Memory Exercise and Instrumental and Vocal Schematic Processing for music lesson instructions and the Five-Letter Name Pitch Memory Test and Three-Chord Familiarization Assessment for basic instrumental music instructions. They are used as a core component deliberately designed to expose classroom teachers and prospective teachers to the essentials for effective instructional practices. Effective evaluation ensures that learners’ knowledge, understanding, and skills are transferred effectively in future contexts.